ERRORS IN USING PREPOSITIONS OF PLACE AND TIME - Tafonao, Masiati (Universitas Nias Raya, 2022)
The use prepositions of place and time in the sentence has been learned at senior high school Hoya Sejahtera. Based on the preliminary study that had been conducted by researcher some of students made errors in using prepositions of place and time. The objectives of this research were to find out the students’ errors in using prepositions of place and time and the reasons causes the errors. This research was designed by used qualitative method. The theory of Miles et al (2014): data condensation, data display, and conclusion drawing conclusion/verifying was used to analyzed the data. The data of this research were collected through documentation and interview. The result of the analysis showed that there were 17 students made error in the use of in, on, at as prepositions of place and time. The errors of the students were caused by lack of knowledge, practice, media of teaching and information. In conclusion, the lack understanding in the use at, on and in as prepositions of place and time will be cause errors. Therefore, it is Suggested that to be familiar in using those prepositions it is needed to create and interesting method in teaching them.